Penerapan Desain Tekstil Pada Perlengkapan Tempat Tidur Bertemakan Identitas Diri Remaja (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2021)
The community's need for decoration in order to beautify a room becomes very important, especially among adolescents in the current generation, namely generation Z. The creation of this work aims to apply the design of textile design products in the form of a set of bedding equipment as a visualization medium for the identity of the Z generation of adolescents. This study uses a qualitative case study research approach. Data collection is done by means of observation, documentation, and questionnaires. The analysis used in the conclusions of this study is the SWOT analysis. The conclusion of the research based on the SWOT analysis can be used as a consideration in determining the sales strategy of textile design products. From the results of a strength research questionnaire in the work that the artist makes, namely illustrating contemporary motifs and using materials that are comfortable and not easily tangled, it creates opportunities for artists' work to be able to compete in the creative industry. The disadvantages of the product that the artist makes are the use of motifs that are too crowded, and the use of synthetic materials that are less environmentally friendly and are flammable. This is a threat because the use of busy motives will slightly interfere with the user's view when going to sleep.